Cynodontium luthii sp. nov.: a permineralized moss gametophyte from the Late Cretaceous of the North Slope of Alaska. Issue 3 (2nd March 2021) - Bippus, Alexander C.; Rothwell, Gar W.; Stockey, Ruth A.
Abstract : PREMISE: Mosses are a major component of Arctic vegetation today, with >500 species known to date. However, the origins of the Arctic moss flora are poorly documented in the fossil record, especially prior to the Pliocene. Here, we present the first anatomically preserved pre‐Cenozoic Arctic moss and discuss how the unique biology of bryophytes has facilitated their success in polar environments over geologic time. METHODS: A permineralized fossil moss gametophyte within a block of Late Cretaceous terrestrial limestone, collected along the Colville River on the North Slope of Alaska, was studied in serial sections prepared using the cellulose acetate peel technique. RESULTS: The moss gametophyte is branched and has leaves with a broad base, narrow blade, and excurrent costa. We describe this fossil as Cynodontium luthii sp. nov., an extinct species of a genus that is known from the High Arctic today. Cynodontium luthii is the oldest evidence of the family Rhabdoweisiaceae (by ≥18 Ma) and reveals that genera of haplolepideous mosses known in the extant Arctic flora also lived in high‐latitude temperate deciduous forests during the Late Cretaceous. CONCLUSIONS: The occurrence of C. luthii in Cretaceous sediments, together with a rich Pliocene‐to‐Holocene fossil record of extant moss genera in the High Arctic, suggests that some moss lineages have exploited their poikilohydric, cold‐ and desiccation‐tolerant physiology to live in the region when it experienced both temperate and freezing climates.